Market Reaction to Information Signals: Evidence from the Indonesian Stock Market - Esi Fitriani Komara; Intan Permata Dewi (Politeknik Siber Cerdika Internasional, 2026)
Background: The capital market is involved in the allocation of funds and the reflection of economic information. However, in emerging markets such as Indonesia, responses to macroeconomic signals are not consistently observed due to information asymmetry, investor heterogeneity, and high economic uncertainty. Objective: This study aims to analyze the impact of interest rates, inflation, and exchange rates on market returns and to describe the response to macroeconomic signals in the Indonesian stock market. Methods: This study uses monthly time-series data from the Indonesia Stock Exchange, Bank Indonesia, and the Central Statistics Agency from 2016 to 2025. Multiple linear regression analysis is used to examine the relationships among the variables. Results: Results show that exchange rates have a negative and significant impact on market returns, while interest rates and inflation have no significant impact on market returns. These findings suggest that external macroeconomic factors, especially currency fluctuations, have a greater impact on stock market reactions than domestic financial variables. Conclusion: This study concludes that among the three macroeconomic information signals analyzed, exchange rates have the most dominant and statistically significant impact on market returns in Indonesia. These findings highlight that market responses in emerging markets are context-dependent and shaped by prevailing macroeconomic conditions and investor risk perceptions.